Evaluation of CPT-based P–y models for laterally loaded piles in siliceous sand. Issue 2 (29th April 2014) - Gavin, K.; Igoe, D.; Li, W.
Abstract : Lateral force–displacement ( P – y )-based Winkler spring models are commonly applied for the design of piles, P being the soil lateral reaction and y the lateral displacement. Despite their relative simplicity, P – y models can capture important aspects of pile behaviour including non-linear soil stiffness. Several P – y models based on cone penetration tests (CPTs) have been proposed over the last two decades, developed largely using empirical curve fitting to results of field tests, centrifuge modelling and finite-element analyses on relatively flexible piles installed in calcareous sand. However, major uncertainties exist when attempting to extrapolate empirical models for use with soil types and pile geometries outside the database on which they were formulated. There is an urgent need for a reliable P – y method for application to the design of rigid monopiles used extensively for offshore wind projects. A series of field lateral load tests performed on open-ended steel pipe piles driven in dense siliceous sand is reported here. The pile embedment length and load eccentricity were varied to investigate the behaviour of rigid and flexible monopiles. The measured pile response was used to evaluate the performance of a number of recent CPT-based P – y models and an update to an existing power-law model is suggested for rigid monopiles in siliceous sand.